Expression and role of nicotinic acetylcholine receptors during midbrain dopaminergic neuron differentiation from human induced pluripotent stem cells - Takeshi Kato; Kaneyasu Nishimura; Masahiro Hirao; Shun Shimohama; Kazuyuki Takata (Wiley, 2023)
Abstract Aim Nicotinic acetylcholine receptors (nAChRs) expressed in midbrain dopaminergic (mDA) neurons modulate mDA neuronal activity. However, their expression patterns and functional roles during mDA neuronal development remain unknown. Here, we profiled the expression and function of nAChR subtypes during mDA neuron differentiation from human induced pluripotent stem cells (hiPSCs). Methods Midbrain dopaminergic neurons were differentiated from hiPSCs using a recently developed proprietary method that replicates midbrain development. The expression patterns of developmental marker proteins were monitored during mDA neuronal differentiation using immunohistochemical analysis. Gene expression of nAChR subtypes was analyzed by reverse transcription polymerase chain reaction. Pharmacological nAChR agonists and antagonists were used to reveal the role of the α6 nAChR subunit in the differentiation of mDA neurons from hiPSCs. Results CHRNA4 expression was detected at the mDA neural progenitor stage, whereas CHRNA6 expression began during the mDA neuronal stage. CHRNA7 was expressed throughout the differentiation process, including in the undifferentiated hiPSCs. We also found that LMO3, a gene expressed in a subset of substantia nigra pars compacta (SNC) DA neurons in the midbrain, showed increased expression following nicotine treatment in a concentration‐dependent manner. Additionally, 5‐iodo A85380, a selective α6 nAChR agonist, also increased LMO3 expression in hiPSC‐derived mDA neurons, and this increase was suppressed by simultaneous treatment with bPiDi, a selective α6 nAChR antagonist. Conclusion Our findings suggest that stimulating the α6 nAChR subunit on hiPSC‐derived mDA neurons may induce neuronal maturation that is biased toward SNC DA neurons.